2023
DOI: 10.1039/d3ra07140e
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic acid chemistry: the past 70 years

Jia-Qi Wang,
Xu Ling,
Hui-Jing Wang
et al.

Abstract: α-Lipoic acid (ALA) is a naturally occurring sulfur-containing fatty acid with high antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
(78 reference statements)
0
3
0
1
Order By: Relevance
“…В процессе исследований взгляды на роль АЛК претерпевали значительные изменения. Если первоначально АЛК рассматривалась лишь в качестве незаменимого кофактора для митохондриальных ферментов, то с открытия ее антиоксидантного действия и до настоящего времени АЛК признается сильным антиоксидантом [3,19]. Большинство последующих исследований АЛК сосредоточено именно на изучении ее антиоксидантных свой ств.…”
Section: Introductionunclassified
“…В процессе исследований взгляды на роль АЛК претерпевали значительные изменения. Если первоначально АЛК рассматривалась лишь в качестве незаменимого кофактора для митохондриальных ферментов, то с открытия ее антиоксидантного действия и до настоящего времени АЛК признается сильным антиоксидантом [3,19]. Большинство последующих исследований АЛК сосредоточено именно на изучении ее антиоксидантных свой ств.…”
Section: Introductionunclassified
“…Structurally, it comprises three components: a five-atom dithiolate ring, an alkyl chain, and a terminal carboxylic acid (see Figure 1 ). The chiral centre at position C6 results in two enantiomers, R(+)-α-lipoic acid, the naturally available form, and S(-)-α-lipoic acid, which can be synthetically obtained [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the extent to which each enantiomer contributes to α-lipoic acid pharmacological and toxicological effects is not fully understood. While it was proposed that S(-)-α-lipoic acid does not exhibit significant biological side effects [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], some studies indicated that it could potentially hinder the activity of the R(-)-enantiomer [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation